Syndemic interactions between HIV/AIDS, mental health conditions, and non-communicable diseases in sub-Saharan Africa: A scoping review of contributing factors - Arvin B. Karbasi; Chukwuemeka Iloegbu; Christina Ruan; Nana Osei-Tutu; Kahini Patel; Leah Frerichs; John Patena; Dorice Vieira; Deborah Adenikinju; Lydia Samuels; Joyce Gyamfi; Emmanuel Peprah (PLoS ONE, 2025)
Introduction The syndemic framework provides a critical lens for understanding the complex interplay between HIV/AIDS, mental health (MH) conditions, and non-communicable diseases (NCDs) in Africa. This scoping review explores how these conditions converge to form a syndemic that disproportionately affects vulnerable populations – particularly people living with HIV/AIDS (PLWH). Contextual factors such as stigma, lower socioeconomic resulting in poverty, gender, resource limitations, and fragmented healthcare systems exacerbate these interrelated conditions, posing significant challenges to individuals and their health. Methods A scoping review was conducted to examine the syndemic interactions between HIV/AIDS, MH, and NCDs across Africa. Utilizing the PRISMA-ScR framework and a predefined inclusion criterion, literature searches were conducted in the following databases: PubMed/Medline (OVID), Web of Science (all databases), Web of Science (core collection), Global Health, Cumulative Index of Allied Health Literature (CINAHL), MEDLINE OVID, Psychinfo (OVID), Psychinfo (proquest); and Psychinfo (psychnet) in March 2024. Articles were screened independently by two peer reviewers and conflicts were resolved by a third reviewer. Data were extracted to summarize study characteristics, prevalence rates, and the contextual factors that underpin syndemic interactions among HIV/AIDS, MH and NCDs. Results An initial search retrieved 5937 articles, with 2913 articles remaining after removal of duplicates. Title and abstract screening further excluded 2706 articles. In total, 207 full-text articles were assessed, of which 17 publications were extracted and included in the review. The scoping review identified a significant prevalence of multi-morbidities amongst PLWH, particularly within hypertension, diabetes, and depression. Women and older adults were disproportionately affected, with gender and age disparities shaping health outcomes. Contextual factors such as stigma, socioeconomic barriers, and fragmented healthcare systems were consistently reported as key contributors to worsening such multi-morbidities. In many publications, NCDs and MH conditions were undiagnosed or poorly managed, complicating HIV treatment and reducing the quality of life. Individual and structural resource limitations, along with poor healthcare integration, further hindered effective care. Conclusion This scoping review underscores the urgent need for integrated healthcare models to address the syndemic of HIV/AIDS, NCDs, and MH in Africa. Interventions should prioritize stigma reduction, capacity building, and comprehensive care to address the underlying socioeconomic determinants of health among PLWH. Strengthening healthcare systems and promoting holistic, patient-centered care is essential for reducing disparities, improving health outcomes, and achieving the Sustainable Development Goals. Future research should expand geographic and demographic coverage to capture the full scope of these syndemic relationships in diverse African contexts.